(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Hospital waste management is an important issue when taken in relevance of overall environmental and public health. In Pakistan, not much attention has yet been focused to assessment of waste management in public or private sector hospitals. Hence we aimed to focus on this problem. Objective: Evaluation of existing waste management situation in public and private health sectors Methodology: This was a cross sectional study conducted in eight public and private hospitals of Lahore. A pre-defined comprehensive questionnaire was made on basis of literature regarding hospitals waste management. The data was entered and analyzed using SPSS 18.0. Detailed descriptive results in form of percentages and ratios were presented. Results: Out of total eight hospitals 6 (75%) hospitals had written hospital waste management plan and 6 (75%) had waste management team. Seven (87.5%) were aware of hospital waste associated risks, 6 (75%) had devised training program. Post exposure procedure after injury was available to 37.5% of the hospitals only, routine surveillance for staff was present in 62.5% hospitals, reporting system on accidents of HMW was present in only 25% (2 of 8). HW weighing was available in 50% (4 of 8) hospitals. Segregation was available in all 8 (100%) hospitals. Hospital waste was disposed of (whether treated or not treated) in pits in 12.5% (1 0f 8) hospital, in municipal dumping sites in 50% hospitals and burned in 3 hospitals (37.5%). Conclusion: Provision of training, reporting of accident injuries, post exposure procedure for injured staff, improvement in collection, transport, storage and safe disposal of waste are deficient areas and need to be improved in all hospitals.